Inhibitory mechanism of two homoisoflavonoids from Ophiopogon japonicus on tyrosinase activity: insight from spectroscopic analysis and molecular docking. Issue 54 (22nd October 2021) - Wang, Liling; Qin, Yuchuan; Wang, Yanbin; Zhou, Yifeng; Liu, Bentong; Bai, Minge; Tong, Xiaoqing; Fang, Ru; Huang, Xubo
Abstract : The inhibition mechanism of two homoisoflavonoids from Ophiopogon japonicus including methylophiopogonanone A (MO-A) and methylophiopogonanone B (MO-B) on tyrosinase (Tyr) was studied by multiple spectroscopic techniques and molecular docking. Abstract : The inhibition mechanism of two homoisoflavonoids from Ophiopogon japonicus including methylophiopogonanone A (MO-A) and methylophiopogonanone B (MO-B) on tyrosinase (Tyr) was studied by multiple spectroscopic techniques and molecular docking. The results showed that the two homoisoflavonoids both inhibited Tyr activity via a reversible mixed-inhibition, with a half inhibitory concentration (IC50 ) of (10.87 ± 0.25) × 10 −5 and (18.76 ± 0.14) × 10 −5 mol L −1, respectively. The fluorescence quenching and secondary structure change of Tyr caused by MO-A and B are mainly driven by hydrophobic interaction and hydrogen bonding. Molecular docking analysis indicated that phenylmalandioxin in MO-A and methoxy in MO-B could coordinate with a Cu ion in the active center of Tyr, and interacted with amino acid Glu322 to form hydrogen bonding, occupying the catalytic center to block the entry of the substrate and consequently inhibit Tyr activity. This study may provide new perspectives on the inhibition mechanism of MO-A and MO-B on Tyr and serve a scientific basis for screening effective Tyr inhibitors.